APPROXIMATION by NONLINEAR FOURIER BASIS in GENERALIZED HÖLDER SPACES - Aslan, Hatice; Guven, Ali (Yildiz Technical University, 2019)
In this paper, the value of deviation of a function f from its nth generalized de la Vallèe-Poussin mean Vna(?, f) with respect to the nonlinear trigonometric system is estimated for the classes of 2?-periodic functions in the uniform norm

C(T) and in the generalized Hölder norm

?? where f ? H??(T) and 0 ? ? < ? ? 1. © 2019 Yildiz Technical University. All Rights Reserved.
Keywords: Generalized de la Vallèe-Poussin means; generalized Hölder class; nonlinear Fourier basis